Back to Osborne. Sequential Protein Extraction and LC-MS Analysis for the Characterization of the Holm Oak Seed Proteome - Romero-Rodríguez, M.Cristina; Maldonado-Alconada, AnaM.; Valledor, Luis; Jorrin-Novo, JesusV. (Plant Proteomics SE - 27, 2014)
It is impossible to capture in just one experiment all or most of the total set of protein species that constitute the cell’s proteome. Thus, according to our results, and even considering that they depend on the experimental system carried out (plant, yeast, fungi, or bacteria), the best protein extraction protocol yielded less than 20 % of the total amount of proteins, as determined by the Kjeldahl method. For this reason, protein cataloguing and the whole proteome characterization require the use of firstly, fractionation techniques at the cellular, subcellular, protein, or peptide level, and secondly, the use of complementary approaches. Within our current research on Holm oak (Quercus ilex subsp. ballota), we aim to characterize its seed proteome. For that we have optimized an experimental workflow in which the Osborne sequential protein extraction (Osborne, Science 28:417–427, 1908) is combined with downstream electrophoretic protein separation or shotgun MS analysis. In general, it can be used to study any plant seed, as well as to investigate on seed maturation and germination, genotype characterization, allergens identification, food traceability, and substantial equivalence, among others.
Keywords: Holm oak proteomics; Osborne; Seed proteomics

Proteotyping of Holm Oak (Quercus ilex subsp. ballota) Provenances Through Proteomic Analysis of Acorn Flour - Valero Galván, José; González Fernandez, Raquel; Valledor, Luis; Rafael Cerrillo, Ma.Navarro; Jorrín-Novo, Jesús V (Methods in Molecular Biology Plant Proteomics SE - 49, 2014)
Proteomics has become a powerful tool to characterize biodiversity and natural variability in plant species, as well as to catalogue and establish phylogenetic relationships and distances among populations, provenances or ecotypes. In this chapter, we describe the standard proteomics workflow that we currently use in cataloguing Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) populations. Proteins are extracted from acorn flour or pollen by TCA/acetone or TCA/acetone-phenol methods, resolved by one- or two-dimensional gel electrophoresis, and gel images are captured and analyzed by appropriate software and statistical packages. Quantitative or qualitative variable bands or spots are subjected to MS analysis in order to identify them and correlate differences in the protein profile with the phenotypes or environmental conditions.
Keywords: Holm oak proteomics; Plant biodiversity; Plant proteotyping